Epidural Space Identification With Loss of Resistance Technique for Epidural Analgesia During Labor: A Randomized Controlled Study Using Air or Saline. Issue 3 (September 2018) - Brogly, N.; Guasch, E.; Alsina, E.; García, C.; Puertas, L.; Dominguez, A.; Diez, Je; Gómez, J.; Gilsanz, F.
Abstract : ( Anesth Analg . 2018;126:532–536) The saline loss of resistance (SLOR) technique was established as the preferred method for epidural space identification in the 1980s, after air LOR (ALOR) was found to have a higher incidence of adverse effects. However, in review of the literature, the authors of the present study discovered that many of the studies had methodological issues. Furthermore, recent meta-analyses based on these studies have been unable to demonstrate superiority of SLOR over ALOR. Consequently, the authors assessed the effect of epidural space identification technique on the onset of anesthetic block, as well as screened for possible variables related to analgesia quality during labor and delivery, which might be affected by use of the ALOR or SLOR technique.